2012
DOI: 10.1016/j.compstruc.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A finite element modelling methodology for the non-linear stiffness evaluation of adhesively bonded single lap-joints: Part 1. Evaluation of key parameters

Abstract: Reported in this paper is the development and verification of a finite element model with the fewest solid elements that can predict the non-linear stiffness characteristics of adhesively bonded single lap-joints in vehicle bodies. This work was driven by the need to significantly reduce computing hardware resources and run times for whole body analyses, and to achieve this goal the lap-joint needs to be modelled by a 'small' number of shell elements. It is wellknown that the deformation of bonded lap-joints i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The reason for this significant difference in stiffness characteristics is the development and activation of localised plastic hinges in the steel at the overlap ends [10].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason for this significant difference in stiffness characteristics is the development and activation of localised plastic hinges in the steel at the overlap ends [10].…”
Section: Introductionmentioning
confidence: 99%
“…From this investigation additional insight into how the stiffness curves change (especially due to adherend flexure and the formation and activation of plastic hinges at the overlap ends) was gained and the parameters essential in FE modelling for determining stiffness with confidence were identified. Using background information from the Part 1 investigations [10] BACKGROUND INFORMATION FROM PART 1 [10] The initial part to the third stage of the research is to consider, and build upon, the background information that is reported in Part 1 [10], so that a decision can be made on whether or not each key parameters (see Figure 1) needs to be represented in the new modelling methodology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations